Partial cut elimination for combinations of propositional multi-modal logics with past time - Sakalauskaitė, Jūratė (Lietuvos matematikos rinkinys, 2011)
We consider combinations of nine propositional multi-modal logics with propositional discrete linear time temporal logic with past time. For these combinations, we present sound and complete Gentzen-type sequent calculi with a restricted cut rule.
Keywords: modal logic; temporal logic; sequent calculus; cut